Development of phenolic electrochemical biosensors using ZrO₂, CeO₂ and ionic liquids-tyrosinase nanocomposites - Ahmad, Nor Monica (2018)
Phenolic compounds are one of the types of pollution that is present in water sources due to the effluents of a various industries such manufacturing, pharmaceutical, resin paint and textile wood. They are included by the Environmental Protection Agency’s (EPA) as part of the priority pollutants due to its persistency and toxicity to the environment. In this study, three biosensors were developed to detect phenolic compounds which is practical to be used for sample in the environment with fast response, high selectivity, cost-effectiveness and simplicity of operation. The development of the phenolic biosensor was carried out by using screen printed carbon electrode (SPCE), hexadecyltrimethylammonium bromide (CTAB) and polyethylene glycol (PEG), zirconium oxide (ZrO2), cerium oxide (CeO2) and 1- butyl-3-methylimidazolium nitrate (BMIMNO3). These biosensors were named as ZrO2/Tyr, ZrO2/BMIMNO3/Tyr and CeO2/BMIMNO3/Tyr. They were similar in the approach of electrode modification and enzyme immobilisation except in the used of different metal oxide and addition of ionic liquid on the electrode surface. The modified electrode was analysed using Scanning Electron Microscope- Energy-dispersive X-ray spectroscopy (SEM-EDX), Electrochemical Impedance Spectroscopy (EIS) and Cyclic Voltammetry (CV). The optimisation for the biosensors were enzyme loading, applied potential, pH, percentage of modifier and volume of nanocomposite that deposited onto the electrode. The biosensors required 10 mg/mL enzyme loading, pH range from 6 – 7, potential range from – 0.10 V until – 0.20 V, 2.0 – 3.0 percent of modifier and 2.0 – 2.5 μL of nanocomposite deposited. These biosensors operated at different potential versus Ag/AgCl which was – 0.20 V and – 0.10 V for ZrO2/Tyr, ZrO2/BMIMNO3/Tyr and CeO2/BMIMNO3/Tyr, respectively. The fastest response time was in the following order: ZrO2/Tyr (10 s) > ZrO2/BMIMNO3/Tyr (15 s) > CeO2/BMIMNO3/Tyr (30 s). The limit of detection (LOD) of the 3 biosensors was found comparable 0.11 μM for ZrO2/Tyr, ZrO2/BMIMNO3/Tyr and CeO2/BMIMNO3/Tyr respectively. The linearity of the biosensor was 0.075 – 55 μM, 0.25 – 30 μM and 0.25 – 40 μM for ZrO2/Tyr, ZrO2/BMIMNO3/Tyr and CeO2/BMIMNO3/Tyr respectively. Sensitivity of the biosensors was found highest for ZrO2/Tyr (219.5 nA/μM followed ZrO2/BMIMNO3/Tyr (133.79 nA/μM) and CeO2/BMIMNO3/Tyr (80.86 nA/μM).